2022
DOI: 10.3390/ijms231810441
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Loci Governing Agronomic Traits and Mutation Hotspots via a GBS-Based Genome-Wide Association Study in a Soybean Mutant Diversity Pool

Abstract: In this study, we performed a genotyping-by-sequencing analysis and a genome-wide association study of a soybean mutant diversity pool previously constructed by gamma irradiation. A GWAS was conducted to detect significant associations between 37,249 SNPs, 11 agronomic traits, and 6 phytochemical traits. In the merged data set, 66 SNPs on 13 chromosomes were highly associated (FDR p < 0.05) with the following 4 agronomic traits: days of flowering (33 SNPs), flower color (16 SNPs), node number (6 SNPs), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…The basic principle of GWAS is to integrate genotype and phenotype data through general linear models or mixed linear models (MLM) [27]. Currently, GWAS have been successfully used with mutants in various crops of interest, including for causal SNPs for agronomic and phytochemical traits in Sorghum bicolor, Brassica napus, and Glycine max [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle of GWAS is to integrate genotype and phenotype data through general linear models or mixed linear models (MLM) [27]. Currently, GWAS have been successfully used with mutants in various crops of interest, including for causal SNPs for agronomic and phytochemical traits in Sorghum bicolor, Brassica napus, and Glycine max [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, advances in next-generation sequencing (NGS) technology have enabled effective sequencing of plant genomes and the direct detection of SNPs, which promotes the development of cultivars of interest in plant breeding [4,16]. GBS reduces the genomic complexity by digesting the genome into small fragments (with restriction enzymes) that are read on a short-read sequencing platform [16,17]. As the availability of entire genome sequences and SNP arrays has increased, association mapping has become a robust approach for determining genetic characteristics, which can significantly increase the precision of quantitative trait locus (QTL)-based position estimates [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…GBS reduces the genomic complexity by digesting the genome into small fragments (with restriction enzymes) that are read on a short-read sequencing platform [16,17]. As the availability of entire genome sequences and SNP arrays has increased, association mapping has become a robust approach for determining genetic characteristics, which can significantly increase the precision of quantitative trait locus (QTL)-based position estimates [17,18]. Moreover, association mapping has been used to overcome the limitations of QTL mapping, particularly because of the large number of SNP markers identified by NGS [16,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Locus-specificity, relative abundance, co-dominant nature, and amenability to high-throughput genotyping make single nucleotide polymorphism (SNP) markers highly desirable for marker-assisted breeding ( Terakami et al., 2011 ). The SNP markers significantly associated with agronomic traits have been reported in rice ( Begum et al., 2015 ; Reig-Valiente et al., 2018 ), wheat ( Rahimi et al., 2019 ), maize ( Sadessa et al., 2022 ), and soybean ( Kim et al., 2022 ). To our knowledge, limited studies have been reported for phenological and yield-associated agronomic traits in mungbean using SNP markers.…”
Section: Introductionmentioning
confidence: 99%